Akuntabilitas Pelecehan Seksual Dilihat Dari Prespektif Perlindungan Anak (Studi Putusan No 142/Pid.Sus/2019/Pn Bna) - Dinda Lestari (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the accountability and punishment of perpetrators of rape in the Decision of the Banda Aceh District  Court Number 142/Pid.Sus/2019/PN-Bna. The verdict failed to provide legal protection for the child victim as mandated by Law Number 35 of 2014. Additionally, the study examines the factors considered by the judge in reaching a verdict in Decision Number 142/Pid.Sus/2019/PN-Bna. The main issue addressed in this journal is how the judge determines the imposition of criminal liability on the perpetrator of child rape (A Study of Decision Number 142/Pid.Sus/2019/PN-Bna), as well as the examination of Law Number 35 of 2014 concerning Child Protection in relation to the criminal liability of rape perpetrators towards their victims. The type of research used is normative legal research. The findings reveal that the panel of judges only imposed criminal sanctions without taking into account the interests of the child as a victim of a criminal act, and failed to uphold protection and justice for the child victim of rape. The decision also did not mention the victim's right to receive compensation and restitution for the perpetrator’s actions, giving the impression that the judge's decision ignored the rights and fate of the victims. Indeed, the sense of justice afforded to the victims in this case was not applied equally. In the case of "intentionally using violence or threats of violence to force a child to engage in sexual intercourse," the judge’s legal considerations in imposing the sentence prioritized the self-rehabilitation of the defendant. According to the criminal provisions in Article 81 paragraph (1) of Law Number 35 of 2014 on Child Protection, perpetrators of child rape are subject to the maximum criminal penalty